(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Studies were carried out on the recent oil spill in the Sundarbans of Bangladesh to findout the immediate impacts on the ecosystem of the Sundarbans after oil spilling. Morethan 500 km2 areas out of the total study area have been affected seriously by the oil spillcontamination on 9 December 2014. Recorded data of the physico-chemical conditions,oil content, productivity, diversity and abundance of phyto-zooplankton and benthos ofwater, and oil content in soil indicate that the water and soil of the Eastern part of theSundarbans were polluted by the oil contamination. Results also indicate that seedlings,mangrove algae, eggs and hatchlings of commercially valuable fishes, mudskippers, mudcrabs, snails, monitor lizards were affected due to oil spill. Regeneration of the Sundritrees; intertidal zone bird - ‘Masked finfoot’, common birds, fishing cat, otter, dolphins,crocodile would be affected due to the oil spill. Long term monitoring, in depth researchand proper implementation of all rules and regulations are necessary to save the fragileecosystem of the Sundarbans-the UNESCO declared world heritage site. Asiat. Soc. Bangladesh, Sci. 41(1): 75-94, June 2015